Poverty Risk among Older Immigrants in a Scandinavian Welfare State - Vibeke Jakobsen; Peder J. Pedersen (Institute for the Study of Labor (IZA), 2016)
Focus in the paper is on poverty among immigrants and refugees 50 years and older coming to Denmark from countries outside the OECD, with main emphasis on immigrants coming as guest workers before 1974, as refugees and as family members and marriage partners – tied movers – relative to individuals coming as guest workers and as refugees. A major share of people in this group were fairly young at arrival to Denmark. Those arriving back in the 1970s and 1980s are now either close to or above the age of 60, with conditional eligibility to a labor market related early retirement program or the age 65 where you become eligible for State pension. Poverty rates by national background are described using alternative household concepts. Next, a number of background factors of relevance for poverty are summarized. We focus on age, gender, marital status, occupational status at age 55 and duration of residence. We find major differences between migrant groups and between migrants and natives regarding how income is composed at different ages on market income, pensions and benefits. Next, we present a number of regressions aiming at explaining differences in the poverty risk with differences in a number of background factors.
Keywords: F22; H55; I32; J14; 330; immigrants; old age poverty; family structure